Robotics in Education Latest Results and Developments (Advances in Intelligent Systems and Computing,, 2018)
This proceedings volume highlights the latest achievements in research and development in educational robotics, which were presented at the 8th International Conference on Robotics in Education (RiE 2017) in Sofia, Bulgaria, from April 26 to 28, 2017. The content will appeal to both researchers and educators interested in methodologies for teaching robotics that confront learners with science, technology, engineering, arts and mathematics (STEAM) through the design, creation and programming of tangible artifacts, giving them the chance to create personally meaningful objects and address real-world societal needs. This also involves the introduction of technologies ranging from robotics controllers to virtual environments. In addition, the book presents evaluation results regarding the impact of robotics on students' interests and competence development. The approaches discussed cover the whole educational range, from elementary school to the university level, in both formal as well as informal settings.